Experiences and notes for research in arts-based psychology - Stubs, Roberta; Teixeira-Filho, Fernando [UNESP]; Galindo, Dolores (FapUNIFESP (SciELO), 2020)
The aim of this article is to consider the creation of a hybrid research/experimentation field at the intersection of contemporary art and psychology. In this sense, we explore the art/experience axis, with the intention of producing singular and sensitive lines of subjectivation. Lines that are more akin to becoming and to the flows than to fixed identities. While individuals/researchers/artists, our proposal was to create metaphors, experiences, images of thoughts and tears in what come to us as ready-made by creating a hybrid figuration/plastic body/subjectivity. This was the way we found to make different intensive surfaces flow. To do so, we followed the Arts Based Research Methodology, and concepts such as figuration, partial connections, located knowledges (Haraway, 1995; 2013), aesthetic subjectivity (Teixeira, 1993; Rolnik, 2002), the logic of sensation (Deleuze, 2002), among others.
Experiencias y apuntes para la investigacion en psicologia basada en las artes
Keywords: Aesthetics subjectivity; Art and psychology; Arts based research; Narrative inquiry